Reducing burnout, vicarious trauma, and secondary traumatic stress through investigating purpose in life in social workers. (September 2020) - Singer, Jonathan; Cummings, Caroline; Moody, Sarah A; Benuto, Lorraine T
Summary: Social workers fulfill vital roles, servicing clients from vulnerable populations and maintaining their welfare. As a result of frequent interaction with clients who have often experienced trauma, these workers are susceptible to experiencing burnout, secondary traumatic stress, and vicarious trauma. This study aimed to identify if purpose in life is a protective factor for adult/elder protective services (AEPS) and child protective services (CPS) workers. A comprehensive search of AEPS and CPS agencies resulted in more than 500 agencies throughout the United States. Three multiple regressions were run, with purpose in life as the independent variable, controlling for social workers' years of experience, ethnicity, average of number of hours worked per week. Findings: A sample of 292 participants ranging in age from 18 to 58 years of age, with a mean age of 42.03(12.34), participated in this study. Of the 292 social workers, 126 reported being CPS workers and 166 reported being AEPS workers. In all three linear regressions, higher purpose in life resulted in lower rates of vicarious trauma ( F (3, 263)=10.364, p< .001), secondary traumatic stress ( F (3, 263)=16.548, p< .001), and burnout ( F (3, 263)= 23.912, p< .001) when controlling for number of hours worked per week and years of experience. The amount of variance explained by these models ranged from 11 to 21%. Post hoc correlations between study variables were conducted, including the association between purpose in life and CS. Applications: This study provides evidence necessary to warrant an intervention for protective services workers, specifically targeted toward increasing purpose in life.